Characterisation of harbour porpoise (Phocoena phocoena) habitat in German waters - Gilles, Anita (Christian-Albrechts-Universität zu Kiel, 2008)
The harbour porpoise (Phocoena phocoena) is an important top predator and as such an indicator species for its environment. Before the beginning of the 21st century, little data existed on distribution and abundance of harbour porpoises in German waters of North and Baltic Sea. As a consequence, virtually nothing was known about important habitats, seasonal differences in distribution and environmental variables determining its distribution. Studies of habitat characteristics of harbour porpoises have been driven both by the need to support conservation and management actions and the increasing availability of suitable tools (e.g. GIS, remote sensing, regression modelling techniques). This thesis aimed to characterise the habitat of harbour porpoises in German waters by estimating abundance, examining spatial and seasonal patterns in distribution, deriving habitat prediction models and investigating the feeding ecology of porpoises in order to infer on predator-prey dynamics. A comprehensive database was set up based on results of aerial surveys conducted year-round in the course of five consecutive years (2002-2006), following standard line transect methodology. Robust abundance estimates for different surveys, that accounted for animals missed on the transect lines, could be derived for the Baltic and the North Sea. In the Baltic Sea, these estimates are especially important to evaluate the effect of bycatch that was found to be a major threat to porpoises throughout the western Baltic Sea. In the North Sea, presented abundance estimates will serve as a baseline for management decisions with respect to the projected construction of large offshore wind farms and its possible impacts on porpoises. Important habitats were detected in offshore waters of the German North Sea: in spring, the two hot spots 'Borkum Reef Ground' and 'Sylt Outer Reef' (SOR) were identified as key foraging areas for harbour porpoises. In summer, the large hot spot SOR persisted, causing a strong north-south density gradient. In autumn, ...